PELAYANAN PUBLIK MELALUI SIMTANAS (SISTEM INFORMASI MANAJEMEN PERTANAHAN NASIONAL) BERBASIS SHORT MESSAGE SERVICE (SMS) PADA KANTOR PERTANAHAN KABUPATEN BADUNG - Kadek Apsariani; I Ketut Artadi (Kertha Negara : Journal Ilmu Hukum, 2014)
At first, the Land Office of Badung Regency has provided the information services manually which was difficult for people who live far from the office to access the information needed. Therefore, this Land institution has made serious efforts toimplement better public services. The data is collected by implementing the normative research method. The purpose of developing this journal is to find out the implementation of public services by the Land Office of Badung Regency in order tocreate a good governance and to find out the implementation of the Instruction of the Head of Land Institution of Indonesia Number 2/Ins/VI/2013 about the services applied in Land institution in Badung regency through SIMTANAS (National Land Management Information System)by SMS (Short Message Service) system to the phone number 081999220666. People are able to question about the progress of their land authority process by sending short message to the number above and is automatically responded by the Land Office of Badung Regency.